Tindak Tutur Imperatif Dialog Talk Show TV One News Episode “Tindakan Asusila, Motif Pembunuhan Brigadir Joshua” - Warda, Firda; Anshari, Anshari; Usman, Usman (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to (1) describe the imperative form of dialogue in the TV One News talk show episode